Can hyperloops substitute high speed rails in the future?. Issue 1 (31st December 2023) - Rajendran, Suchithra; Sinha, Akhouri Amitanand
Abstract : While the existing literature has focused on the impact of High Speed Rails (HSR) on the airline industry, we believe that this research is the first to examine the substitutability of HSR with Hyperloop services from an operational point of view. A simulation model is developed to compare the performance of both these alternate transportation modes for a network of three major cities in Europe (Amsterdam, Paris, and Frankfurt). Our results indicate that with a significantly lower pod capacity, the Hyperloop system will still be able to serve more customers compared to the HSR services, while the vehicle utilization is observed to be higher in the latter alternative for a given period of time. In addition, sensitivity analysis is conducted to assess the impact of variation in capsule capacity, number of pods in the system, and commuter variability. We further compare the two transportation modes with respect to their estimated infrastructure and operational costs as well as CO2 emission. Finally, a cost–benefit analysis is conducted to evaluate the passenger ticket price for Hyperloop services.